PERKARA IZIN POLIGAMI DI PENGADILAN AGAMA BENGKALIS (Analisis Terhadap Putusan Hakim Nomor: 0307/Pdt.G/2017/PA.Bkls) - Khairil Anwar; Sri Ikamulia (JURIS (Jurnal Ilmiah Syariah), 2019)
This study aims at determining the basic considerations of the Panel Judges in Bengkalis Religious Court in granting Polygamy Permit to case Number: 0307/Pdt.G / 2017 /PA.Bkls. Additionally, this study also to find out the normative juridical review of this Judge's Decision. The results of this study indicate that this polygamy permit application is only eccomplish the cumulative requirements, but does not eccomplish the alternative conditions. Therefore honestly this application should have been rejected. However, the Bengkalis Religious Court in this case granted the application by using the Contra Legem principle in order to fill the legal vacuum on the basis of the mudhorot or harmfulness which contained in this case. This is excatly in accordance with the fiqhiyah method: "Iza Ta'arodho Mafsadatani Ru'iya" Adhohuma Dhororon Birtikabi Akhofuha "which means that if there are two cases that are equally harmful or degrading, then it must be safeguarded by a greater degree of harmfulness, by working on a lighter Mudharat or the danger.